Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Formula is: $((p \wedge q) → r) \wedge (¬(p \wedge q) → r)$

This is what I've already done:

$$((p \wedge q) → r) \wedge (¬(p \wedge q) → r)$$

$$(¬(p \wedge q) \vee r) \wedge ((p \wedge q) \vee r)$$

$$((¬p \vee ¬q) \vee r) \wedge ((p \wedge q) \vee r)$$

And from this point I'm not sure how to proceed. Help would be appreciated.

Sorry, but the last line was written badly(I think). It's fixed now.

share|cite|improve this question
It's really great you got as far as you did; thanks for showing what you've done. – amWhy Nov 4 '12 at 17:10
up vote 6 down vote accepted

You can continue by using Distributivity of the boolean algebra:

$((¬p \vee ¬q) \vee r) \wedge ((p \wedge q) \vee r)$

$ \Leftrightarrow (¬p \vee ¬q \vee r) \wedge ((p \wedge q) \vee r)$

Here we apply distributivity:

$ \Leftrightarrow (¬p \wedge p \wedge q) \vee (¬q \wedge p \wedge q) \vee (r \wedge p \wedge q) \vee (¬p \wedge r) \vee (¬q \wedge r) \vee (r \wedge r)$

Formally, this is in disjunctive normal form now. We could further simplify:

$ \Leftrightarrow (r \wedge p \wedge q) \vee (¬p \wedge r) \vee (¬q \wedge r) \vee r$

share|cite|improve this answer
Sorry for asking, but how did you use distributivity law to get the third line? All I can think of is to use this identity: a∧(b∨c)=(a∧b)∨(a∧c) to get this: ((¬p∨¬q∨r)∧(p∧q))∨((¬p∨¬q∨r)∧r) – user1242967 Nov 6 '12 at 18:39
Here you use: (a∨b∨c)∧(d∨e)=(a∧d)∨(b∧d)∨(c∧d)∨(a∧e)∨(b∧e)∨(c∧e) – user48415 Nov 6 '12 at 18:59
The above can be seen as follows: (a∨b∨c)∧(d∨e) = ((a∨b∨c)∧d) ∨ ((a∨b∨c)∧e) = (a∧d)∨(b∧d)∨(c∧d)∨(a∧e)∨(b∧e)∨(c∧e) – user48415 Nov 6 '12 at 19:06
brother, how did you simplified further the last statement using disjunctive normal form – Humoyun Jun 23 at 4:07

((p∧q)\to r)∧(¬(p∧q)\to r) ⇔(¬(p∧q)∨r)∧((p∧q)∨r) using distributive law: ⇔r∨(¬(p∧q)∧(p∧q)) ⇔r∨F (because s∧¬s equals false)

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.